2022
DOI: 10.1055/s-0041-1740974
|View full text |Cite
|
Sign up to set email alerts
|

Severe Skin and Soft-Tissue Infections

Abstract: Skin and soft-tissue infections (SSTIs) are a common reason for hospital admission. Severe SSTIs, particularly necrotizing infections, often require intensive care. Source control (often with surgical debridement) and broad-spectrum antimicrobials are paramount for minimizing significant morbidity and mortality. Rapid diagnostic tests may help in selection and de-escalation of antimicrobials for SSTIs. Besides early source control and early effective antimicrobial therapy, other patient-level factors such as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The most widespread recommendation is to perform surgery within 12 h of admission to ensure prompt treatment [50,66,67 ▪ ]. It is crucial to act quickly, as delayed surgical intervention is associated with higher comorbidities and mortality rates [68–70,71 ▪▪ ]. Even though patients requiring source control may have more severe illnesses, studies have shown that source control is associated with reduced mortality and length of stay [70,72].…”
Section: Introductionmentioning
confidence: 99%
“…The most widespread recommendation is to perform surgery within 12 h of admission to ensure prompt treatment [50,66,67 ▪ ]. It is crucial to act quickly, as delayed surgical intervention is associated with higher comorbidities and mortality rates [68–70,71 ▪▪ ]. Even though patients requiring source control may have more severe illnesses, studies have shown that source control is associated with reduced mortality and length of stay [70,72].…”
Section: Introductionmentioning
confidence: 99%
“…The immune status of some patients has been shown to be important in the clinical outcomes of some, but not all, types of SSTIs. The debate regarding the benefits of intravenous immunoglobulin continues to be waged in recent literatures [ 6 ].…”
mentioning
confidence: 99%